2020
DOI: 10.3389/fmicb.2020.562491
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spvC Gene Inhibits Pyroptosis and Intestinal Inflammation to Aggravate Systemic Infection in Mice

Abstract: Salmonella enterica serovar Typhimurium (S). Typhimurium is a primary foodborne pathogen infecting both humans and animals. Salmonella plasmid virulence C (spvC) gene is closely related to S. Typhimurium dissemination in mice, while the mechanisms remain to be fully elucidated. Pyroptosis, a gasdermin-mediated inflammatory cell death, plays a role in host defense against bacterial infection, whereas the effect of spvC on pyroptosis and its function in inflammatory injury induced by S. Typhimurium are rather li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…We next examined the effect of the Salmonella spvC gene on intracellular bacterial loads. In agreement with our previous studies in vivo (18), macrophages J774A.1 infected with STM-DspvC showed significantly lower bacterial burden than those infected with STM-WT or STM-DspvC/pspvC since 2 hpi in vitro (Figure 1C). The aforementioned results suggest spvC restricts elimination of pathogens in host cells which may be related to its contribution to autophagy, while the underlying mechanism remains elusive.…”
Section: Results Spvc Suppresses Autophagy and Increases Intracellular Survival Of Salmonella Typhimurium In Macrophages At The Early Stasupporting
confidence: 93%
See 2 more Smart Citations
“…We next examined the effect of the Salmonella spvC gene on intracellular bacterial loads. In agreement with our previous studies in vivo (18), macrophages J774A.1 infected with STM-DspvC showed significantly lower bacterial burden than those infected with STM-WT or STM-DspvC/pspvC since 2 hpi in vitro (Figure 1C). The aforementioned results suggest spvC restricts elimination of pathogens in host cells which may be related to its contribution to autophagy, while the underlying mechanism remains elusive.…”
Section: Results Spvc Suppresses Autophagy and Increases Intracellular Survival Of Salmonella Typhimurium In Macrophages At The Early Stasupporting
confidence: 93%
“…We demonstrated that spvC affects the formation of autophagosomes in an ERK dependent manner. Besides we have proved that spvC inactivates phospho-ERK1/2, phospho-JNK and phospho-p38, leading to the interference of NLRP3 and NLRC4 in S. Typhimurium infected macrophages J774A.1 (18). Given all this, whether JNK and p38 are involved in spvC suppressed autophagy remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The majority of important gene-encoded virulence factors are mainly located on pathogenicity islands (SPIs), which are highly conserved in Salmonella ( Michael et al, 2006 ). Several genes are important in Salmonella virulence, included inv A, spv C spa N, sip B, and sop B, are associated with the ability to invade the intestinal epithelial cells ( Klein et al, 2000 ; Liebl et al, 2017 ; Zuo et al, 2020 ; Krishna and Dhanashree, 2021 ). The outbreak strains also carried a series of genes associated with adhesion ( lefA-E ), colonization ( Rat B and Sin H) and biofilm formation ( csgA- G), which promote invasion and survival of strains in unsuitable environments ( Desai et al, 2019 ; Elkenany et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of important gene-encoded virulence factors are mainly located on pathogenicity islands (SPIs), which are highly conserved in Salmonella (Michael et al, 2006). Several genes are important in Salmonella virulence, included invA, spvC spaN, sipB, and sopB, are associated with the ability to invade the intestinal epithelial cells (Klein et al, 2000;Liebl et al, 2017;Zuo et al, 2020;Krishna and Dhanashree, 2021). The outbreak strains also carried a series of genes associated with adhesion (lefA-E), colonization (RatB and SinH) and biofilm formation (csgA-G), which promote invasion and survival of strains in unsuitable environments (Desai et al, 2019;Elkenany et al, 2019).…”
Section: Discussionmentioning
confidence: 99%